PENGARUH MODEL PEMBELAJARAN GAMIFIKASI BERBANTUAN PERANGKAT PEMBELAJARAN BERBASIS WEB TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS IV SDN 3 MENANGA KABUPATEN KARANGASEM - I Made Oka Kembarisna; Ni Made Muliani; Kd Jayanthi Riva Prathiwi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The process of learning Indonesian in grade IV at SDN 3 Menanga is still dominated by the conventional one-way method which triggers students' boredom with long narrative story texts, thus having an impact on low motivation and cognitive achievement in reading comprehension of students who have not met the KKM. This study aims to test the influence of gamification learning models assisted by web-based learning tools on the learning outcomes of Indonesian language reading materials, comprehension of narrative texts for grade IV students of SDN 3 Menanga, Karangasem Regency. The research method used was quantitative experiment with One-Group Pretest-Posttest Design. Through the saturated sampling technique, all 31 students in grade IV of SDN 3 Menanga were involved as research samples. Data were collected using randomly selected objective test instruments to minimize the testing effect. Data analysis used the Shapiro-Wilk normality prerequisite test on Unstandardized Residual values and hypothesis test through the SPSS 27-assisted Paired Sample t-Test. The results of the data analysis proved that there was a very significant influence, as shown by the acquisition of a significance value (Sig. 2-tailed) of 0.001 < 0.05, so that H0 was rejected and Ha was accepted. Descriptively, this positive influence is evidenced by a surge in the classical average score from 57.94 during the pretest to 82.06 during the posttest, accompanied by a massive increase in the level of learning completeness reaching 77.42% or as many as 24 students successfully completed the KKM. The conclusion of the study confirms that the web-based gamification model integrated with the Interactive Flat Panel (IFP) has proven to be effective in improving the learning outcomes of Indonesian language for elementary school students.